Alha Udal Ballad Rendition of Western Uttar Pradesh : A War Rendition of India - Pathak, Amit (Brill | Manohar Publishers & Distributors, 2024)
Alha Udal ballad is a military folk rendition traditionally sung in large parts of northern and central India. It carries traditions, terms and idioms of nearly nine hundred years of collective memory of residents of Haryana in the north-west to Bihar in the east, and is sung in several dialects that stretch through this vast landscape. The present book is dedicated to the Khari Boli variant of the rendition which was sung in Western Uttar Pradesh, Delhi and Haryana, with some overlap over the adjoining Brajbhasha cultural zone. Throughout our historical past, citizen soldiers were the backbone of all the armed forces of the sub-continent, working as farmers and herders during peacetime and as soldiers of the empire, the king or military generals when called out during times of war. It was folk renditions like Alha Udal that instilled in these citizens the requisite martial traits, transforming them into tough and seasoned soldiers with a will to fight and bear all adversities which they encountered with bravery and fortitude. This military rendition that prepared the residents of these lands to become soldiers from an early age, was thus instrumental in evolving a strong martial culture in India, the impact of which can be felt even today. The rendition is therefore an integral part of Project Udbhav that seeks to study and document the long history of Indian military and strategic thought and traditions.